1990
DOI: 10.1007/bf01871568
|View full text |Cite
|
Sign up to set email alerts
|

Identification of riboflavin transport by MDCK cells using quantitative fluorescence video microscopy

Abstract: MDCK cells, when examined by low-light level video microscopy displayed an endogenous fluorescence with two differing patterns. A low intensity emission which was punctate and associated with cell organelles was observed with emission and excitation conditions generally used to observe either fluorescein (450-500 nm excitation/greater than 510 nm emission) or rhodamine (514 nm excitation/greater than 530 emission) type dyes. A second 5- to 10-fold brighter emission for 450-500 nm excitation was observed, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…3A). This is in concordance with the accumulation of riboflavin in basolateral spaces and fluid-filled "domes" of MDCK-II cells (15) and may reflect the mechanism(s) responsible for reabsorption of riboflavin in the kidney and possibly in the intestine (9,20). Bcrp1 is apically located and should transport its substrates to the apical side of the monolayer, possibly counteracting the endogenous absorptive process (19).…”
Section: Consequences Of Absence Of Bcrp1 Expression In the Mammary Gsupporting
confidence: 72%
“…3A). This is in concordance with the accumulation of riboflavin in basolateral spaces and fluid-filled "domes" of MDCK-II cells (15) and may reflect the mechanism(s) responsible for reabsorption of riboflavin in the kidney and possibly in the intestine (9,20). Bcrp1 is apically located and should transport its substrates to the apical side of the monolayer, possibly counteracting the endogenous absorptive process (19).…”
Section: Consequences Of Absence Of Bcrp1 Expression In the Mammary Gsupporting
confidence: 72%
“…In addition, the subject of riboflavin excretion has gained increasing attention. Jusko et al (18,19) and others (7,25,40,45) demonstrated saturable renal reabsorption and accumulation of riboflavin. Therefore, riboflavin transporters are thought to be essential for the maintenance of riboflavin homeostasis in the intestine and kidney.…”
mentioning
confidence: 95%
“…Although AF originating from the cytoplasmic region of mammalian cells has been studied by many researchers (Andersson et al, 1998;Aubin, 1979;Benson et al, 1979;Bondza-Kibangou et al, 2001;Croce et al, 1999;DaCosta et al, 2005;Georgakoudi et al, 2002;Matsui et al, 1998;Mayeno et al, 1992;Reinert et al, 2004), AF from plasma membranes of viable intact cells, less known and not thoroughly investigated, has been mentioned only in a few older reports (Lowy and Spring, 1990;Nokubo et al, 1988Nokubo et al, , 1989. These early reports did not provide detailed information about the spectral properties of the described AF.…”
Section: Introductionmentioning
confidence: 82%
“…It has been postulated that membrane AF was due to the presence of riboflavin transported to cells (Lowy and Spring, 1990). However, it is difficult to understand how a constant concentration of free riboflavin would be maintained by the cell in the region close to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation